Letramento digital contextualizado : uma experiência na formação continuada de professores - Souza, Valeska Virgínia Soares (2007)
In the context of new technologies used in educational environments, our research has proposed the investigation of a course for the digital literacy of EFL English teachers. It was a course module added to the in-service program English for All Pro, which has been attended by public school teachers from the state of Minas Gerais. At first, we supposed that, after the digital literacy course, the attending teachers, once exposed to the use of tools available through the computer and the Internet, would be able to demonstrate a more autonomous and more competent use of the various tools available in the computer and the Internet in their professional development and in the process of class preparation. We investigated if there really was competent use of the technological resources by these participants and which could be the impact of such a course on teachers actions. Despite the vast universe studied, we were theoretically supported, mostly, by researches in the area of Applied Linguistics, with emphasis on foreign language teaching and learning (BROWN, 2000; HARMER, 1991, 1998; NUNAN, 1999, 2001; among others), new technologies (BUZATO, 2001a, 2001b, 2006; COSCARELLI; RIBEIRO, 2005; GILSTER, 1997; PAIVA, 2001, 2006a, 2006b; WARSCHAUER, 1997; among others) and teacher education (CELANI, 2003; KLEIMAN, 1995, 2001; among others). Considering there is an interdisciplinary dialogue among social and human sciences, our study is also founded on researchers from the areas of Linguistics (CRYSTAL, 2001; among others), Education (FREIRE, 1990, 1996; SOARES, 2002, 2003, 2005; among others) and Philosophy (LÉVY, 1993, 1996, 1998; among others). We have adopted the premises of Integral Action Research to our interpretive paradigm research. The data were collected and analyzed in three phases, in a spiral process. The research tools that we applied for further data triangulation were: (i) semi-structured pre-course questionnaire, (ii) test on English language knowledge, (iii) test on metalinguistic knowledge, (iv) video recording and field notes for the face-to-face tasks, (v) electronic register of virtual tasks, and (vi) semi-structured post-course questionnaire. The analyses were conducted at the light of a matrix we designed for the process of contextualized digital literacy. The data were analyzed with a focus on four macro-competencies: interactivity, autonomy, interaction and collaboration. The main conclusions point to the fact that the digital literacy process depicts itself as multiple and complex, and the interdependence of the analyzed macro-competencies result in a super-competency, which we have named contextualized digital literacy. These reflections, allied to the observation of the participants development throughout the research, enabled us to critically review the matrix presented a priori. It was partially proved that the course participants have used the available technological resources with more competence and more autonomy, which does not mean that these teachers cannot be considered digitally literate.